Três obras de câmara de Heitor Villa-Lobos (1887-1959) analisadas sob o ponto de vista da parte da flauta à luz dos manuscritos do Museu Villa-Lobos: Choros nº 2 (1924), Quinteto em Forma de Choros (1928), e Bachianas Brasileiras nº 6 (1938) - Rubem Eloy Schuenck (2017)
The present work presents a study on three works by Heitor Villa-Lobos (1887-1959): Choros No. 2 (1924) for flute and clarinet, Quinteto em Forma de Choros (1928), and Bachianas Brasileiras no. 6 (1938) for flute and bassoon. Based on the manuscripts and the flute parts, we focused on his writing for this instrument and also in the influence that the popular urban music on the composition of these works. We aim to provide technical and interpretative subsidies that may assist in the interpretation and analysis of these pieces.